Komunikasi Korporasi dalam Menjalin Hubungan dengan Dunia Usaha dan Dunia Industri (DUDI) untuk Meningkatkan Kualitas Peserta Didik - Purnomo, Agustina; Safitri, Selvia; Kusumadinata, Ali Alamsyah (Universitas Djuanda Bogor, 2024)
Ideally, Vocational High School (SMK) serves as an educational institution dedicated to equipping individuals with the skills and knowledge necessary for a smooth transition into the workforce. However, many vocational school graduates are unemployed. Therefore, to deal with this problem, vocational schools need to implement good corporate communication with DUDI in order to improve the quality of their students. This research aims to determine the objectives and corporate communication strategies used by the Industrial Relationship section of SMK Amaliah 1 and 2 Ciawi to DUDI and the impact on improving the quality of students. This research method uses qualitative methods with interview, observation and documentation data collection techniques. Interview sessions were held with four informants. The results of this research show that the corporate communication carried out by SMK Amaliah 1 and 2 Ciawi aims to persuade DUDI to collaborate. Apart from that, SMK Amaliah 1 and 2 Ciawi applies the RACE strategy model to carry out its communication so that the school is able to improve the quality of students through learning media, teacher competency, learning facilities and the curriculum used.